SOA REFERENCE ARCHITECTURE BLUEPRINT - . Edison; Virginia Tulenan; Ford Lumban Gaol (Faculty of Computer Science Universitas Indonesia, 2009)
Service Oriented Architecture (SOA) is a framework for integrating business processes and supporting IT infrastructure as secure, standardized components services that can be reused and combined to address changing business priorities. Services are the building blocks of SOA and new applications can be constructed through consuming these services and orchestrating services within a business process. In SOA, services is map to the business functions that are identified during business process analysis. Upon a successful implementation of SOA, the enterprise gain benefit by reducing development time, utilizing flexibility and responsive application structure, and following dynamic connectivity of application logics between business partners. This paper presents SOA reference architecture blueprint as the building blocks of SOA which is services, service components and flows that together support enterprise business processes and the business goals. Layanan Berorientasi Arsitektur (SOA) merupakan framework untuk mengintegrasikan proses bisnis dan mendukung infrastruktur TI secara aman, layanan komponen standar yang dapat digunakan kembali dan dikombinasikan untuk mengatasi perubahan prioritas bisnis. Layanan merupakan blok bangunan SOA, di mana aplikasi baru dapat dibangun melalui konsumsi layanan ini dan merancang layanan dalam proses bisnis. Dalam SOA, layanan dipetakan ke fungsi bisnis yang diidentifikasi selama analisis proses bisnis. Setelah keberhasilan implementasi SOA, perusahaan memperoleh keuntungan diantaranya mengurangi waktu pengembangan, memanfaatkan fleksibilitas dan struktur aplikasi responsif, dan mengikuti konektivitas dinamis dari logika aplikasi antara mitra bisnis. Paper ini menyajikan cetak biru referensi arsitektur SOA sebagai blok bangunan SOA yang merupakan komponen pelayanan jasa, dan arus yang bersama-sama mendukung proses bisnis perusahaan dan tujuan bisnis.